Organizational and legal contexts of cooperative security: from global trends to local forecasts - Vivchar, Oksana; Drakokhrust, Tetiana; Muzhylivskyi, Nazar (Actual problems of law (Aktual’ni problemi pravoznavstva), 2024)
The concept and organizational and legal contexts of ensuring cooperative security hav been examined in this article. Three main approaches to the practical basis of applying the components of this security concept have been presented. As a result of scientific research, the main global vectors of the development of cooperative security have been determined. The general characteristics of the concept of cooperative security in the context of practical applications of the «security triangle» have been demonstrated. On this basis, the application of relevant practical-oriented aspects regarding the implementation of relevant countermeasures in order to ensure the security of the state is determined. It was established that in modern conditions there is a constant need to find the most effective model or concept of international security. It should be noted that there is no perfect solution, as security requires reconciling the expectations of individual states with very different statuses and interests.